Urgency Arrangement Accountability Criminal Corporations Over the Abuse of Artificial Intelligence In Cyber Crime in Indonesia - Siti Hapsah Fahira; Rio Rinaldy (Sekolah Tinggi Agama Islam Kuningan, 2026)
The development of Artificial Intelligence (AI) has create transformation big in life social, economic, and global digital systems. However, the use of AI also gives rise to risk abuse in various form action criminal cyber such as deepfakes, personal data theft, automated phishing, manipulation digital information, up to attack cyber based algorithm. Complexity AI technology raises challenge new in system law Indonesian criminal law, in particular related accountability criminal corporation as developers, owners, and organizer system electronic AI- based research This aim For analyze urgency arrangement accountability criminal corporation on misuse of AI in action criminal cyber in Indonesia. The research method used is juridical normative with approach legislation and approaches conceptual. Research results show that arrangement law in Indonesia is still nature partial and not yet in a way specific arrange accountability criminal corporation to action criminal AI- based. The gap in the norm potential cause uncertainty law in enforcement law cyber. Therefore that, is necessary reformulation policy law criminal through strengthening AI regulation, harmonization between the Criminal Code, the ITE Law, and the PDP Law, as well as implementation the principle of strict liability and vicarious liability against corporation. Research This confirm that comprehensive regulation is urgent For ensure certainty law, protection society and security room cyber national.